On the stability and mobility of di-vacancies in tungsten. (19th December 2017) - Heinola, K.; Djurabekova, F.; Ahlgren, T.
Abstract: Properties of small vacancy clusters in tungsten were studied with first-principles calculations. The binding and formation energies of the vacancy clusters increase with the cluster size. Dynamic characteristics of a di-vacancy were specified between room temperature and 700 K with lattice kinetic Monte Carlo calculations, which were parametrised with the present first-principles results for the dissociation barriers. An Arrhenius fit for the di-vacancy diffusion yielded D = 0.04 exp ⁡ ( − 1.65 e V k T − 1 ) c m 2 s − 1, and for the mean lifetime, τ = 0.093 exp ⁡ ( 1.7 e V ) k T − 1 ps. The di-vacancy system was found to be stable up to 500 K, due to the high energy needed for its dissociation. Having a carbon impurity was found to increase the tungsten di-vacancy binding energy.